2020
DOI: 10.1371/journal.pone.0240509
|View full text |Cite
|
Sign up to set email alerts
|

Mobility improvement of patients with peripheral visual field losses using novel see-through digital spectacles

Abstract: To evaluate see-through Augmented Reality Digital spectacles (AR DSpecs) for improving the mobility of patients with peripheral visual field (VF) losses when tested on a walking track. Design Prospective Case Series. Participants 21 patients with peripheral VF defects in both eyes, with the physical ability to walk without assistance. Methods We developed the AR DSpecs as a wearable VF aid with an augmented reality platform. Image remapping algorithms produced personalized visual augmentation in real time base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…In the face recognition task, participants identified faces at over 75% of accuracy with 100 lm pixels and only 2 grayscale levels. In addition, both Sayed et al 70 and Kinateder et al 71 reported improved object recognition when participants used their respective AR device ( P < 0.001 for both).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In the face recognition task, participants identified faces at over 75% of accuracy with 100 lm pixels and only 2 grayscale levels. In addition, both Sayed et al 70 and Kinateder et al 71 reported improved object recognition when participants used their respective AR device ( P < 0.001 for both).…”
Section: Resultsmentioning
confidence: 91%
“…Nineteen studies evaluated the use of VR and AR in treatment/therapy as seen in Supplementary Digital Content, Table 4, http://links.lww.com/APJO/A96. [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]…”
Section: Treatment/therapymentioning
confidence: 99%
See 1 more Smart Citation
“…There are also devices with visual displays that transform information to present it in a format that is more accessible to particular groups of partially sighted users. For instance, augmented reality digital spectacles [ 65 ] use digital video reprocessing algorithms involving image remapping and data on the user’s visual field to expand the functional visual field of people with reduced visual fields. The algorithm might need to be separately calibrated for each user.…”
Section: Head-mounted Devicesmentioning
confidence: 99%
“…Other research studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] reveal few documented cases of eye tracking techniques used to evaluate the usability of AR systems in the last 20 years. In evaluations of more traditional computer-based technology (e.g., web sites, computer applications), eye tracking has proven to be an invaluable tool.…”
Section: Introductionmentioning
confidence: 99%